2014
DOI: 10.4103/0253-7613.132158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative oral sildenafil on severe pulmonary artery hypertension in patients undergoing mitral valve replacement

Abstract: Aim:Long standing mitral valve disease is usually associated with severe pulmonary hypertension. Perioperative pulmonary hypertension is a risk factor for right ventricular (RV) failure and a cause for morbidity and mortality in patients undergoing mitral valve replacement. Phosphodiesterase 5 inhibitor-sildenafil citrate is widely used to treat primary pulmonary hypertension. There is a lack of evidence of effects of oral sildenafil on secondary pulmonary hypertension due to mitral valve disease. The study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The following is the description of the included studies. Table 1 summarizes the characteristics and details of the included studies [20-22]. All studies were conducted in different tertiary hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following is the description of the included studies. Table 1 summarizes the characteristics and details of the included studies [20-22]. All studies were conducted in different tertiary hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted in different tertiary hospitals. In the study by Ayyad et al [21], the mean age was 32 ± 10.4 years with more women in the placebo group; in the study by Gandhi et al [22], the mean age was 38.79 ± 8.62 years with 50% men; and in the study by Shim et al [20], the mean age was 50 ± 11.5 years with 39% men. Almost all the patients in the three studies underwent elective mitral valve replacement due to either mitral stenosis or mitral regurgitation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gandhi et al showed in a clinical trial with 40 patients that suffered from severe PH that were scheduled for mitral valve replacement that sildenafil administered before surgery reduced PH and the need for mechanical ventilation compared to placebo [ 53 ].…”
Section: Treatmentmentioning
confidence: 99%